2021
DOI: 10.1055/s-0040-1706039
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Arylphosphorothiolates as Convergent Substrates for Ar-SF4Cl and Ar-SF5 Synthesis

Abstract: In this manuscript we describe the oxidative fluorination of aryl phosphorothiolates to access Ar-SF4Cl compounds. These compounds serve as precursors for the highly coveted Ar-SF5 compounds. The use of phosphorothiolates as starting materials permits access to Ar-SF4Cl from a wide variety of available starting materials, namely boronic acids, diazonium salts, aryl iodides, thiophenols, or simple arenes. The protocol has been demonstrated for >10 examples and showed good tolerance to various functional grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Following the acquired results, we were satisfied to observe that an 19 F NMR yield of 87% could be obtained for 4a employing DPDS (0.50 mmol), TCICA (4.50 mmol), and KF (32 mmol) in dry MeCN (4.3 mL) at room temperature in the gas-generation chamber and using 3a (0.67 mmol) and Et 3 B (0.07 mmol) in dry n -hexane (2.7 mL) at −94 °C in the gas-consumption chamber. Under these conditions, a shorter reaction time (9 h) gave superior results compared to the typical reaction times (18–48 h) for an optimal KF/TCICA-mediated chlorotetrafluorosulfanylation established in the literature. , Moreover, the method is compatible with different solvents like CH 2 Cl 2 and Et 2 O and nonpolar n -hexane, creating a suitable solubility profile for the employment of a wider range of starting materials. To acquire a better prospect on the yield of the generated SF 5 Cl gas, we conducted one experiment under the optimized conditions in the absence of 3a and Et 3 B while cooling the hexane-containing chamber to −94 °C from the beginning (for 9 h).…”
mentioning
confidence: 86%
“…Following the acquired results, we were satisfied to observe that an 19 F NMR yield of 87% could be obtained for 4a employing DPDS (0.50 mmol), TCICA (4.50 mmol), and KF (32 mmol) in dry MeCN (4.3 mL) at room temperature in the gas-generation chamber and using 3a (0.67 mmol) and Et 3 B (0.07 mmol) in dry n -hexane (2.7 mL) at −94 °C in the gas-consumption chamber. Under these conditions, a shorter reaction time (9 h) gave superior results compared to the typical reaction times (18–48 h) for an optimal KF/TCICA-mediated chlorotetrafluorosulfanylation established in the literature. , Moreover, the method is compatible with different solvents like CH 2 Cl 2 and Et 2 O and nonpolar n -hexane, creating a suitable solubility profile for the employment of a wider range of starting materials. To acquire a better prospect on the yield of the generated SF 5 Cl gas, we conducted one experiment under the optimized conditions in the absence of 3a and Et 3 B while cooling the hexane-containing chamber to −94 °C from the beginning (for 9 h).…”
mentioning
confidence: 86%
“…The oxidative fluorination is achieved either with chlorine gas as the stoichiometric oxidant in the presence of KF, introduced by Umemoto et al (9,10) or with solid chlorinating reagent TCICA, as reported by Togni and Shibata. (11,12) Due to these advances, the interest of the synthetic organic community in pentafluorosulfanylation and its related chemistry has been re-ignited recently (13)(14)(15)(16)(17)(18)(19)(20)(21) and novel SF5-pharmaceuticals have appeared in clinical trials and patents. (22)(23)(24) However, the total efficiency of the current synthetic route toward Ar-SF5 compounds remains unsatisfactory due to several associated problems: a multi-step synthetic sequence; overall low to moderate yields; difficulty in handling of intermediates due to strong smell and/or moisture sensitivity; limitations in substrate scope (e.g.…”
Section: Main Textmentioning
confidence: 99%
“…Another significant improvement made possible by this methodology is the use of ozone non‐depleting Solkane 365/227 [31,37] . Recently, Shibata and Cornella employed AgBF 4 as an easy‐to‐handle and stable source of fluorine for the chlorine‐fluorine exchange reaction with good results ( 24 m in Scheme 8, F) [32b,38] …”
Section: Synthesis Of R–sf5 Compounds and Analogs Via S−f Bond Formationmentioning
confidence: 99%